Mesa redonda: ¿Derecho administrativo económico, regulación o derecho regulatorio? - Falla Jara, Alejandro (2025)
This roundtable examines one of the central debates in contemporary public law: the relationship between economic administrative law, regulation, and the possible existence of a “regulatory law” as an autonomous branch.One position maintains that no such conceptual distinction exists, as regulation is a multidisciplinary phenomenon whose legal application is carried out through the proper techniques to administrative law. In contrast, another view offers a more nuanced interpretation. It distinguishes between economic administrative law as a legal discipline, and regulation as a specific technique of intervention applied to strategic sectors or those with structural failures.Based on this distinction, it is argued that although regulation is rooted in public law, it exhibits certain modulations that warrant independent consideration. The debate, without doubt, offers the reader a rich confrontation of ideas.